Effect of Feeding Concentrate Mixture Containing Varying Levels of Cashew Nut Kernel Meal on Nutrient Utilization in Ram Lambs - Balaga, Sravani; Konka, Raja Kishore; Dhulipalla, Srinivas Kumar; Matha, Kalyana Chakravarthi (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was conducted to assess the effect of feeding concentrate mixture containing varying levels of cashew nut kernel meal (CNKM) on nutrient utilization in ram lambs. Eighteen ram lambs were randomly divided into three equal groups of six each and allotted to three dietary treatments (T1 to T3) comprising of green fodder viz., Super Napier and concentrate mixture (20% CP) containing CNKM at 0, 10 and 20%, respectively. The average DMI of ram lambs was comparable among treatments. Significantly higher (P<0.05) digestibility (%) of DM, OM, CP, EE, CF, NFE, NDF, ADF and cellulose was observed in ram lambs of group T3 compared to control, while the difference in hemicellulose was non-significant. The TDN content expressed as % in diet consumed was higher (p<0.05) in T3 compared to control, while the difference in DCP (%) in the diet consumed was not significant. The estimated DE and ME intakes (Mcal/d) increased (p<0.05) with increased level of CNKM in the concentrate mixture, while there was no significant difference in the intakes of DM, DCP, TDN and ME per kgW0.75.